Main Portal Vein Diameter Changes in Patients Undergoing Gastric Surgery for Malignancy: An Observational CT Study - Gündoğdu, Elif; Bayav, Fatma Didem; Karakaya, İhsan Burak; Türker, Barış; Özer, İlter (Indian Journal of Radiology and Imaging, 2023)
Background In the follow-up computed tomography (CT) examinations of patients who had undergone gastrectomy for gastric malignancy in our center, we noticed by chance that there was an isolated increase in the diameter of the main portal vein (MPV) without other radiological findings of portal hypertension.Objectives In this study, we aimed to evaluate whether the MPV diameter of patients who had gastric surgery for malignancy differed in the preoperative and postoperative periods and its change over time in patients who underwent postoperative follow-up examinations.Materials and Methods The CT images of 240 patients who underwent abdomen CT for staging and follow-up gastric malignancy between January 2017 and September 2021 were evaluated retrospectively. The CT scans of the remaining 149 patients after the exclusion criteria were included in the study. All CT imaging was performed using multidetector CT (64 or 128 slice) in portal venous phases. The images were evaluated by two radiologists based on consensus. Maximum MPV diameter were measured outer wall to outer wall with calipers on axial images at the level of 1 cm distal to the portosplenic confluence.Results One hundred forty-nine patients included in the study had preoperative CT examination. Eighty-three patients had follow-up CT examination at third month, 89 patients at sixth month, and 99 patients at first year. The MPV diameters differed significantly between preoperative CT and postoperative third month, sixth month, and first year CT (p = 0.001, p = 0.001, and p = 0.001, respectively). There was no difference in MPV diameter between postoperative third month CT and postoperative 6th month and 1st year CT (p = 0.514 and p = 0.078, respectively).Conclusion There is an increase in MPV diameter in the first 3 months postoperatively in patients undergoing gastric surgery for malignancy. This enlargement continues unchanged in the first 1 year follow-up. The radiologists' awareness of this situation may prevent the wrong diagnosis of portal hypertension, unnecessary concern, and further investigation.
Keywords: main portal vein diameter; computed tomography; gastric surgery